2020
DOI: 10.1080/2578983x.2019.1662595
|View full text |Cite
|
Sign up to set email alerts
|

Do crime hot spots affect housing prices?

Abstract: Our knowledge about what happens to housing values when properties are close to places with high concentrations of crime, often called 'hot spots', is limited. Previous research suggests that crime depresses property prices overall, but crime hot spots affect house prices more than crime occurrence does and may affect prices of single-family houses more than prices of flats. Here we employ hedonic price modelling to estimate the impact of crime hot spots on housing sales, controlling for property, neighbourhoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 51 publications
(68 reference statements)
0
20
0
2
Order By: Relevance
“…Some studies have found this to be the case. For example, Lynch and Rasmussen (2001) find that for Jacksonville as a whole crime had virtually no effect on house prices overall, while Ceccato and Wilhelmsson (2020) reached the same conclusion for Stockholm. Gibbons (2004) finds that for London as a whole, criminal damage lowers housing prices, while burglary and housing prices are not related.…”
Section: Why Should Income Inequality Affect House Prices?mentioning
confidence: 82%
See 1 more Smart Citation
“…Some studies have found this to be the case. For example, Lynch and Rasmussen (2001) find that for Jacksonville as a whole crime had virtually no effect on house prices overall, while Ceccato and Wilhelmsson (2020) reached the same conclusion for Stockholm. Gibbons (2004) finds that for London as a whole, criminal damage lowers housing prices, while burglary and housing prices are not related.…”
Section: Why Should Income Inequality Affect House Prices?mentioning
confidence: 82%
“…The pricing impact of crime is complex and varies by type of crime, property type, and location (McIlhatton et al, 2016). Most of the literature that studies the effect of crime on house prices is about local areas and finds that crime leads to a decrease of house prices in crime hotspots -less demand-and an increase in house prices in neighboring areas, which tend to see an inflow of residents that leave crime hotspots (Ceccato & Wilhelmsson, 2020).…”
Section: Why Should Income Inequality Affect House Prices?mentioning
confidence: 99%
“…Kim & Kim, 2020;Leinberger & Alfonzo, 2012), greenery (Ye et al, 2019;Y. Zhang & Dong, 2018), openness (Chen et al, 2020;Fu et al, 2019), safety (Ceccato & Wilhelmsson, 2020;Naik et al, 2014), aesthetics (Cetintahra & Cubukcu, 2015;Jim & Chen, 2009;Quercia et al, 2014), and risks (McCluskey & Rausser, 2001) in a neighborhood all have correlations with residents' everyday behaviors, psychological perceptions of the place, wiliness to pay, and eventually the surrounding property values.…”
Section: Selection Of the Six Perceptual Qualitiesmentioning
confidence: 99%
“…Zhang et al, 2018). Prior studies implied that in districts perceived as being less safe from surveys (Buonanno et al, 2013) or with higher crime rates (Ceccato & Wilhelmsson, 2020), houses are highly discounted. However, how perceived safety from street appearance will affect house prices has not been clearly stated in literature.…”
Section: Selection Of the Six Perceptual Qualitiesmentioning
confidence: 99%
“…Crime concentration is a key element for designing and measuring crime reduction strategies (Rogerson 2008 ), accounting for the public health burden (Carter et al. 2019 ) and detecting the impacts of crime on the real estate market (Ceccato and Wilhelmsson 2020 ) among many. The fact that crime concentrates among some individuals or is perpetrated only by a limited number of people also impacts prevention programs and is a crucial driver of fear of crime (Prieto Curiel and Bishop 2017 ).…”
Section: Introductionmentioning
confidence: 99%